The Impact of Inter‐ICU Transfer Timing on Clinical and Economic Outcomes. (15th September 2021) - Nadig, Nandita; Brinton, Daniel; Simpson, Kit; Simpson, Annie; Goodwin, Andrew; Ford, Dee
Abstract : Research Objective: To examine the impact of transfer timing on in‐hospital mortality, hospital length of stay (LOS), and cumulative charges on acute respiratory failure (ARF) patients. Study Design: We conducted a retrospective, quasi‐experimental study utilizing Healthcare Cost Utilization Project databases (HCUP‐SID) in 5 states (FL, MD, MS, NY, WA) during 2015–2017. To control for potential selection bias, we propensity score matched patients (1:1) to model propensity for early transfer using a priori defined patient demographics, clinical, and hospital variables that influence the probability of inter‐ICU transfer. Doubly‐robust multivariable modeling was used to examine the impact of transfer timing on in‐hospital mortality, hospital length of stay (LOS), and cumulative charges. Population Studied: Patients with ICD‐10 codes for respiratory failure and mechanical ventilation who underwent an inter‐ICU transfer, grouping as early (≤ 2 days) and delayed transfers (3+ days). Principal Findings: 6718 patients with ARF underwent inter‐ICU transfer, 68% of whom (n = 4552) were transferred early (≤ 2 days). Propensity score matching yielded 3774 well‐matched patients for this study. Unadjusted outcomes were all lower in the early vs. delayed transfer cohort: in‐hospital mortality (24.4% vs. 36.1%; p < 0.0001), length of stay (8 vs. 22 days; p < 0.0001), and cumulative charges (118, 686 vs. 308, 977; p < 0.0001). Through fully‐adjusted multivariable modeling, we found patients who were transferred early had 66% lower odds of in‐hospital mortality than those whose transfer was delayed (OR 0.34, 95% CI: 0.29–0.40). Additionally, the early transfer cohort had lower LOS [6.8 fewer days (10.8 vs. 17.6; p < 0.001)], and lower cumulative charges [94, 471 less (207, 211 vs. 301, 682; p < 0.001)]. Conclusions: Our study is the first to use a large, multi‐state sample to evaluate the practice of inter‐ICU transfers in ARF. This definition of early and delayed transfers is also distinct from past work, which has more commonly grouped all transfers together. The main finding of our study is that early transfers have a 66% decrease in mortality. These findings are vital in designing prospective studies evaluating evidence‐based transfer procedures, policies, and guidelines. Implications for Policy or Practice: Acute respiratory failure (ARF) leads to 2.5 million ICU admissions annually, resulting in over 30% mortality with an estimated cost of 27 billion. Current data estimates that 1 in 30 patients with ARF will undergo an inter‐ICU transfer, typically to receive a higher level of care. Although implications of inter‐ICU transfer are varied, there are currently no studies evaluating the impact of timing of transfer on outcomes. Our study suggests earlier ICU transfer may yield lower mortality rates, decreased LOS, and cumulative charges. The study however implies only associations and not causation which will need to be evaluated in future studies. Primary Funding Source: National Institutes of Health.